PENGARUH JANUARY EFFECT TERHADAP RETURN SAHAM, ABNORMAL RETURN DAN TRADING VOLUME ACTIVITY PADA SAHAM INDEKS LQ – 45 DI BURSA EFEK INDONESIA - Dinda Mutiasari; V. Santi Paramita (Prosiding Working Papers Series In Management, 2018)
January effect is one of the seasonal anomalies that can occur in the capital market. January effect is a condition where in January the average return of stock is higher than month other than January. The purpose of this study is to determine the condition of stock return, abnormal return, and trading volume activity between January and month other than January. Other objective is to know stock return, abnormal return and trading volume activity in January tends to be higher than month other than January (happened January effect). This research is conducted on LQ-45 index of stock group in Indonesia Stock Exchange (BEI) year 2013-2016. The object of research in this research is stock return, abnormal return, and trading volume activity. Sampling technique using purposive sampling method so that obtained 22 companies selected become sample research. Hypothesis testing is done by paired sample t-test. The results of this test indicate that stock return, abnormal return, and trading volume activity between January and month other than January there is no difference, it can be concluded January Effect phenomenon does not occur in Indonesia Stock Exchange in LQ-45 Index stock group Year 2013-2016 .Keywords: Seasonal anomaly, January effect, stock return, abnormal return, trading volume activity